(untitled) (SOUTH ARAL SEA MEDICAL JOURNAL, 2025)
The study investigated the significance of clinical and laboratory parameters and cystatin C levels in assessing renal dysfunction in patients with liver cirrhosis. A total of 90 patients and 30 healthy controls were examined. Patients with renal dysfunction showed significantly increased creatinine, urea, and cystatin C levels, with a decreased glomerular filtration rate (p<0.05). Cystatin C demonstrated a negative correlation with GFR and a positive correlation with creatinine and urea. The findings suggest that cystatin C may serve as an additional marker for early detection and prognostic evaluation of hepatorenal syndrome.